Apple puree's texture is independent from fruit firmness. (June 2021) - Buergy, Alexandra; Rolland-Sabaté, Agnès; Leca, Alexandre; Renard, Catherine M.G.C.
Abstract: How cellular and molecular structure of raw fruits impact puree's texture is still an unresolved question. Texture variations of purees obtained from four apple cultivars of contrasted texture (Braeburn, Gala, Golden Delicious, Granny Smith) and two modalities (mealiness, fruit load) after two contrasted processes were investigated. Although puree's viscosity strongly varied between cultivars (562–1368 mPa s), it did not correlate with apple firmness, except for Granny Smith. This cultivar had the firmest fruits (3.2 N) and the most viscous purees (1368 mPa.s), in accordance with large particles (around 650 μm), high pulp wet mass and serum viscosity. Mealy Braeburn apples showed lower puree's viscosity (562 mPa.s) than their not-mealy homologues (779 mPa.s). This was due to reduced cell adhesion, maybe because of lower (arabinose + galactose)/rhamnose ratio, leading to smaller particles during processing. Process also impacted puree's viscosity (692–939 mPa s), with more viscous purees obtained with the high temperature-low shear process. Highlights: Fruit firmness could not predict puree's viscosity. Cultivars highly affected puree's viscosity. Granny Smith revealed particularly high fruit and puree's textures. Mealy apples generated less viscous purees because of reduced cell adhesion. High temperature-low shear process produced more viscous purees.